PENGARUH KUALITAS PRODUK DAN EFEKTIFITAS IKLAN TERHADAP NIAT PEMBELIAN KOSMETIK PONDS DI KOTA AMBON - Tanihattu, Maudy Marla (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
AbstractThis study aims to identify and analyze how much influence adverstising effectiveness and product quality on purchase intentions of Ponds Cosmetics in Ambon Town.The data was collected using questionnaires with Likert scale and the sampling method used was accidental sampling of 100 samples. The analytical method used was multiple linear regression (multiple linear regression).From the results of the regression analysis has been done on the factors that influence consumers intentions to buy the Ponds cosmetics in Ambon Tow are Product Quality and Advertising Effectiveness.Keywords: Quality of Products, Advertising Effectiveness, Purchase Intention